Biosynthesis of silver nanoparticles for the fabrication of non cytotoxic and antibacterial metallic polymer based nanocomposite system - Sadaf Raza; Asma Ansari; Nadir Naveed Siddiqui; Fariha Ibrahim; Muhammad Ishaque Abro; Afsheen Aman (Scientific Reports, 2021)
Abstract Nanomaterials have significantly contributed in the field of nanomedicine as this subject matter has combined the usefulness of natural macromolecules with organic and inorganic nanomaterials. In this respect, various types of nanocomposites are increasingly being explored in order to discover an effective approach in controlling high morbidity and mortality rate that had triggered by the evolution and emergence of multidrug resistant microorganisms. Current research is focused towards the production of biogenic silver nanoparticles for the fabrication of antimicrobial metallic-polymer-based non-cytotoxic nanocomposite system. An ecofriendly approach was adapted for the production of silver nanoparticles using fungal biomass (Aspergillus fumigatus KIBGE-IB33). The biologically synthesized nanoparticles were further layered with a biodegradable macromolecule (chitosan) to improve and augment the properties of the developed nanocomposite system. Both nanostructures were characterized using different spectrographic analyses including UV–visible and scanning electron microscopy, energy dispersive X-ray analysis, dynamic light scattering, and Fourier transform infrared spectroscopic technique. The biologically mediated approach adapted in this study resulted in the formation of highly dispersed silver nanoparticles that exhibited an average nano size and zeta potential value of 05 nm (77.0%) and − 22.1 mV, respectively with a polydispersity index of 0.4. Correspondingly, fabricated silver–chitosan nanocomposites revealed a size of 941 nm with a zeta potential and polydispersity index of + 63.2 mV and 0.57, respectively. The successful capping of chitosan on silver nanoparticles prevented the agglomeration of nanomaterial and also facilitated the stabilization of the nano system. Both nanoscopic entities exhibited antimicrobial potential against some pathogenic bacterial species but did not displayed any antifungal activity. The lowest minimal inhibitory concentration of nanocomposite system (1.56 µg ml−1) was noticed against Enterococcus faecalis ATCC 29212. Fractional inhibitory concentration index of the developed nanocomposite system confirmed its improved synergistic behavior against various bacterial species with no cytotoxic effect on NIH/3T3 cell lines. Both nanostructures, developed in the present study, could be utilized in the form of nanomedicines or nanocarrier system after some quantifiable trials as both of them are nonhazardous and have substantial antibacterial properties.